A MAX phase ceramic-metal-high temperature alloy based self-lubricating composite sleeve and its preparation method
By filling the sleeve with self-lubricating material of MAX-phase ceramic-metal components to form a composite sleeve, the problem of coordination and uniformity of mechanical properties and self-lubricity of the existing sleeve in high temperature environment is solved, and efficient self-lubricating and wear resistance are achieved.
Patent Information
- Application Number
- CN202411157537.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-08-22
AI Technical Summary
The existing shaft sleeves are difficult to combine high-temperature mechanical properties and high-temperature self-lubricity in high-temperature, complex loads and high friction environments, and cannot meet the service needs in heavy-duty equipment.
The MAX phase ceramic-metal-high temperature alloy-based self-lubricating composite shaft sleeve is used to set up a housing cavity in the main structure of the sleeve to fill the self-lubricating material of the MAX phase cermet component and the metal component to form a self-lubricating structure, and the combination of the two is achieved through sintering treatment.
It realizes a composite bushing with high mechanical properties and low friction characteristics in extreme high temperature environments, extends the service life of the bushing and provides effective support, lubrication and protection in complex environments.
Smart Images

Figure CN119035555B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of shaft sleeves, and in particular to a MAX phase ceramic-metal-high temperature alloy based self-lubricating composite shaft sleeve and a preparation method thereof. Background Art
[0002] In recent years, the rapid development of heavy equipment such as generators, engines, and gas turbines has brought a series of new challenges to the service performance of sliding bearing components. Especially for key components such as internal sleeves, bushings, and piston rings, they will face high-temperature oil-free lubrication over 600°C and high-friction service environments with complex high-stress loads for a long time. In order to ensure the important functions of good support, stability, and life extension for shaft parts, the relevant sleeves need to have both high-temperature strength and high-temperature anti-friction performance. Traditional liquid and solid lubricating materials often have insufficient high-temperature mechanical properties and cannot meet the service requirements of high-temperature and heavy-load friction environments. Therefore, it is urgent to research and develop a new generation of high-temperature solid lubricating sleeves that can work in complex environments such as high temperature, high pressure, and high load. The metal alloy, ceramic, and composite material-based solid lubricating sleeves reported so far are difficult to achieve the coordinated unification of high-temperature mechanical and high-temperature tribological properties. It is urgent to develop a new type of metal-based self-lubricating sleeve with high temperature, high strength, and low friction to meet the service requirements under high temperature and high load. Summary of the invention
[0003] The object of the present invention is to provide a MAX phase ceramic-metal-high temperature alloy based self-lubricating composite shaft sleeve having both good high temperature mechanical properties and high temperature self-lubricating properties and a preparation method thereof.
[0004] In a first aspect, the present invention provides a MAX phase ceramic-metal-high temperature alloy based self-lubricating composite sleeve, the composite sleeve comprising a sleeve main body structure and a self-lubricating structure, the sleeve main body structure is provided with a receiving cavity to be filled, and the self-lubricating material is filled and compounded in the receiving cavity of the sleeve main body structure to form the self-lubricating structure;
[0005] Wherein, the main structure of the sleeve is made of a high-temperature alloy material, and the high-temperature alloy material includes at least one of a Ni-based, Co-based, Fe-based, Ti-based, Mo-based, Nb-based or intermetallic compound-based high-temperature alloy;
[0006] The self-lubricating material comprises a MAX phase cermet component and a metal component;
[0007] The molecular formula of the MAX phase metal ceramic component is M n+1 AX n, n=1, 2 or 3, M includes at least one of Ti, V, Cr, Zr, Nb, Mo, Hf, Sc or Ta, A includes at least one of Al, Si, P, S, Ga, Ge, As, Cd, In, Sn, Tl or Pb, and X is C and / or N;
[0008] The metal component includes at least one of metals Cu, Ag, Pb, Ti, Al or V.
[0009] Optionally, the accommodating cavity includes at least one of a hole, a groove or an interpenetrating network pore structure provided on the main structure of the sleeve, and the total volume of the accommodating cavity accounts for 10 to 70% of the total volume of the main structure of the sleeve.
[0010] Optionally, the total volume of the accommodating cavity accounts for 20-50% of the total volume of the sleeve main structure.
[0011] Optionally, the mass ratio of the MAX phase metal ceramic component to the metal component is 0.5:99.5 to 99.5:0.5.
[0012] Optionally, the high-temperature alloy material includes a Ni-based high-temperature alloy.
[0013] Optionally, the MAX phase metal ceramic component includes Ti3AlC2 and / or doped (Ti,M')3AlC2, wherein M' includes at least one of Cr, V, Zr or Nb; the metal component includes Cu and / or Cu-M" alloy, wherein M" includes at least one of Ni, Sn, Cr, Nb, Ag, Pb, Ti or Al.
[0014] Optionally, a transition layer is formed between the shaft sleeve main body structure and the self-lubricating structure, and the average thickness of the transition layer is 3 to 30 μm.
[0015] Optionally, the phase structure of the transition layer includes a Cu / Ni phase and a Ni / Ni3Al phase.
[0016] In a second aspect, the present invention provides a method for preparing a MAX phase ceramic-metal-high temperature alloy based self-lubricating composite sleeve, comprising the following steps:
[0017] S1. Providing a sleeve main structure and a self-lubricating material, wherein the sleeve main structure is provided with a receiving cavity to be filled, and the self-lubricating material is filled in the receiving cavity of the sleeve main structure;
[0018] S2. Sintering and molding to prepare the self-lubricating composite sleeve, wherein the self-lubricating material is compounded in the accommodating cavity of the sleeve main structure to form a self-lubricating structure.
[0019] Optionally, in step S2, the sintering pressure is 30-1000 MPa, the sintering temperature is 700-1300° C., and the holding time is 5-200 min.
[0020] Optionally, in step S2, the sintering pressure is 30-100 MPa, the sintering temperature is 850-1000° C., and the holding time is 5-30 min.
[0021] In summary, the present invention has at least one of the following beneficial effects:
[0022] 1. The present invention provides a composite shaft sleeve with good high-temperature mechanical properties, high high-temperature stability, and high-temperature lubrication and wear resistance. The high-temperature and high-strength self-lubricating composite shaft sleeve has broad application prospects in extreme high temperature, complex load, impact, and high-temperature friction environments.
[0023] 2. The present invention realizes the metallurgical reaction bonding between the main structure of the high-temperature alloy sleeve and the MAX phase-based self-lubricating structure, and the two can form a strong interface bonding. At the same time, the metallurgical bonding between the two structures ensures the synergistic performance of their respective performances and the overall strength of the composite sleeve. The prepared composite sleeve uses a high-strength high-temperature alloy as the main structure of the sleeve, which ensures that the sleeve has good mechanical properties from room temperature to high temperature environments. The MAX phase-based self-lubricating material is filled on the friction surface of the sleeve to form a self-lubricating structure. Its own multi-layered microstructure and high-temperature stability ensure that the sleeve has good high-temperature self-lubricating effect and wear resistance on the friction surface. In summary, this type of composite sleeve has the comprehensive performance of both high-temperature alloys and high-temperature solid lubricating materials, and can effectively support, lubricate, stabilize and protect the bearing system over a wide temperature range. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 Schematic diagram of the structure of different self-lubricating composite sleeves according to the embodiments of the present invention;
[0026] Figure 2 This is a physical picture of the self-lubricating composite sleeve with an outer diameter of 20 mm sintered at 900° C. in Example 1;
[0027] Figure 3 This is the interface microstructure of the self-lubricating composite sleeve with an outer diameter of 20 mm sintered at 900°C in Example 1;
[0028] Figure 4is the friction coefficient curve between the inner surface of the self-lubricating composite sleeve with an outer diameter of 20 mm sintered at 900° C. and the high-temperature alloy in Example 1;
[0029] Figure 5 is the friction coefficient curve between the inner surface of the self-lubricating composite sleeve with an outer diameter of 30 mm sintered at 900° C. and the high-temperature alloy in Example 2;
[0030] Figure 6 This is the interface microstructure of the self-lubricating composite sleeve with an outer diameter of 30 mm sintered at 1000°C in Example 3. DETAILED DESCRIPTION
[0031] The present invention provides a MAX phase ceramic-metal-high temperature alloy based self-lubricating composite sleeve and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] High-temperature alloys refer to a type of metal material based on iron, nickel, cobalt, titanium, molybdenum, niobium or intermetallic compounds that can work for a long time at high temperatures above 600°C and under certain stresses. High-temperature alloys have good high-temperature strength, high-temperature oxidation resistance and corrosion resistance, as well as good fatigue performance, fracture toughness and other comprehensive properties, and are mainly used in the aerospace field. Taking the engine in the aerospace industry as an example, as the flight speed continues to increase, the engine weight ratio will need to be greater, the engine load will also become larger and larger, and the ambient temperature will become higher and higher. Especially for key components such as sleeves, bushings and piston rings in the machine, lubricating oils and greases in high-temperature environments are easily diluted, and they will face high-temperature oil-free lubrication above 600°C and high-friction service environments with complex high-stress loads for a long time. Research reports show that the development of wear-resistant materials with self-lubricating properties under high-temperature conditions has important application value for improving the high-temperature wear resistance of kinematic pairs. After long-term research, the inventor has creatively proposed a MAX phase ceramic-metal-high temperature alloy based self-lubricating composite sleeve and a preparation method thereof. The sleeve consists of a high temperature alloy based sleeve main structure and a self-lubricating filling structure. The sleeve main structure is a high-strength and high-temperature structural material with a straight groove, an inclined groove or an inner hole in a shape of semicircular, U-shaped, V-shaped, square, dovetail, etc. to be filled; the self-lubricating filling structure is a MAX phase ceramic (M n+1 AX n, M is a pre-transition metal, A is an A group element, X is carbon and / or nitrogen, n = 1,2,3) and a metal material composed of a high-temperature self-lubricating material; after sintering, the two are combined to finally form a composite sleeve with high-temperature and high-strength self-lubricating properties, ensuring that the composite sleeve has high mechanical properties as a whole under high-temperature oil-free lubrication conditions, while the friction surface still has self-lubricating, low-friction and low-wear properties, and the sleeve has a long service life. This type of sleeve can support, fix, protect and lubricate the shaft in complex environments such as high temperature, oxidation resistance and load impact, ensuring that various action components can operate normally. The present invention is obtained on this basis.
[0033] In some embodiments of the present invention, a MAX phase ceramic-metal-high temperature alloy based self-lubricating composite sleeve is provided, the composite sleeve comprising a sleeve main body structure and a self-lubricating structure, the sleeve main body structure is provided with a receiving cavity to be filled, and the self-lubricating material is filled and compounded in the receiving cavity of the sleeve main body structure to form the self-lubricating structure;
[0034] Wherein, the main structure of the sleeve is made of a high-temperature alloy material, and the high-temperature alloy material includes at least one of a Ni-based, Co-based, Fe-based, Ti-based, Mo-based, Nb-based or intermetallic compound-based high-temperature alloy;
[0035] The self-lubricating material comprises a MAX phase cermet component and a metal component;
[0036] The molecular formula of the MAX phase metal ceramic component is M n+1 AX n , n=1, 2 or 3, M includes at least one of Ti, V, Cr, Zr, Nb, Mo, Hf, Sc or Ta, A includes at least one of Al, Si, P, S, Ga, Ge, As, Cd, In, Sn, Tl or Pb, and X is C and / or N;
[0037] The metal component includes at least one of Cu, Ag, Pb, Ti, Al or V. The metal may be a single metal or an alloy.
[0038] In some embodiments of the present invention, the intermetallic compound-based high-temperature alloy includes at least one of a Ni3Al-based intermetallic compound high-temperature alloy, a NiAl-based intermetallic compound high-temperature alloy, a Ti3Al-based intermetallic compound high-temperature alloy, a TiAl-based intermetallic compound high-temperature alloy and a Fe3Al-based intermetallic compound high-temperature alloy.
[0039] In some embodiments of the present invention, the high-temperature alloy material includes a Ni-based high-temperature alloy; preferably, the MAX phase metal ceramic component M includes at least one of Ti, V, Cr, Zr, and Nb; A includes at least one of Al, Si, P, S, Ga, or Pb; more preferably, the MAX phase metal ceramic component includes Ti3AlC2 and / or doped (Ti, M')3AlC2, wherein M' includes at least one of Cr, V, Zr, or Nb; the metal component includes Cu and / or Cu-M" alloy, wherein M" includes at least one of Ni, Sn, Cr, Nb, Ag, Pb, Ti, or Al; more preferably, the MAX phase metal ceramic component includes Ti3AlC2, and the metal component includes Cu.
[0040] In some embodiments of the present invention, the accommodating cavity includes at least one of a hole, a groove or an interpenetrating network pore structure arranged on the sleeve main body structure, and the total volume of the accommodating cavity accounts for 10 to 70% of the total volume of the sleeve main body structure; preferably, the total volume of the accommodating cavity accounts for 20 to 50% of the total volume of the sleeve body; more preferably, the total volume of the accommodating cavity accounts for 25 to 40% of the total volume of the sleeve body; more preferably, the total volume of the accommodating cavity accounts for 26 to 33% of the total volume of the sleeve body.
[0041] In some embodiments of the present invention, the mass ratio of the MAX phase metal ceramic component to the metal component is 0.5:99.5 to 99.5:0.5; preferably, the mass ratio of the MAX phase metal ceramic component to the metal component is 20:80 to 80:20; more preferably, the mass ratio of the MAX phase metal ceramic component to the metal component is 30:70 to 70:30.
[0042] In some embodiments of the present invention, a transition layer is formed between the sleeve main structure and the self-lubricating structure, and the average thickness of the transition layer is 3 to 30 μm; preferably, the average thickness of the transition layer is 5 to 20 μm; more preferably, the average thickness of the transition layer is 8 to 12 μm.
[0043] In some embodiments of the present invention, the phase structure of the transition layer includes a Cu / Ni phase and a Ni / Ni3Al phase.
[0044] In some embodiments of the present invention, a method for preparing a MAX phase ceramic-metal-high temperature alloy based self-lubricating composite sleeve is provided, comprising the following steps:
[0045] S1. Providing a sleeve main structure and a self-lubricating material, wherein the sleeve main structure is provided with a receiving cavity to be filled, and the self-lubricating material is filled in the receiving cavity of the sleeve main structure;
[0046] S2. Sintering and molding to prepare the self-lubricating composite sleeve, wherein the self-lubricating material is compounded in the accommodating cavity of the sleeve main structure to form a self-lubricating structure.
[0047] In some embodiments of the present invention, in step S2, the sintering pressure is 30-1000 MPa, the sintering temperature is 700-1300°C, and the holding time is 5-200 min; preferably, the sintering pressure is 30-100 MPa, the sintering temperature is 850-1000°C, and the holding time is 5-100 min; more preferably, the sintering pressure is 40-80 MPa, the sintering temperature is 870-970°C, and the holding time is 5-20 min.
[0048] In some embodiments of the present invention, please refer to Figure 1 , Figure 1 The figure shows a possible structural schematic diagram of a composite sleeve, wherein the composite sleeve includes a sleeve main structure and a self-lubricating structure. The sleeve main structure is a circular ring structure, and the inner surface is provided with straight grooves, oblique grooves or porous accommodating cavities to be filled with cross-sections of semicircular, U-shaped, V-shaped, square, etc.; the self-lubricating material is filled in the accommodating cavity of the sleeve main structure, and the self-lubricating material includes a MAX phase metal ceramic component and a metal component. After the filling is completed, sintering is performed to prepare the composite sleeve, and the self-lubricating material is compounded in the accommodating cavity of the sleeve main structure to form a self-lubricating structure.
[0049] In some embodiments of the present invention, the MAX phase metal ceramic component can be pure metal ceramic, or it can be doped with a small amount of the second type of compound, the second type of compound includes nitride (Si3N4, AlN, etc.), boride (TiB2, ZrB2, etc.), oxide (Al2O3, MoO3), sulfide (MoS2, WS2, etc.) or intermetallic compound (Ti3Al, Ni3Al, etc.). The addition of the hard second type of compound with high melting point and high shear strength that is difficult to oxidize will play a role of dispersion strengthening, improving the strength of the composite sleeve at high temperature, but it may be detached under the action of the grinding pair during the friction process, forming abrasive particles, and increasing the volume wear rate of the composite sleeve; while the addition of low melting point oxides or the addition of the second type of compound that oxidizes to form low melting point oxides during the friction process will improve the self-lubricating properties of the composite sleeve, such as TiB2 will form B3O2 during high temperature friction, reducing the friction coefficient and volume wear rate.
[0050] The present invention is further described below by means of specific examples. In the specific examples of the present invention, raw materials are commercially available unless otherwise specified, or are obtained by conventional preparation methods in the art.
[0051] Example 1
[0052] This embodiment provides a MAX phase ceramic-metal-high temperature alloy based self-lubricating composite sleeve and a preparation method thereof, comprising the following steps:
[0053] S1. Provide a shaft sleeve main structure and self-lubricating material. The shaft sleeve main structure is made of high-temperature alloy material. The high-temperature material of Example 1 adopts Incol738 nickel-based high-temperature alloy. The outer diameter of the shaft sleeve main body is 20 mm, the inner diameter is 16 mm, and the height is 3 mm. The inner ring of the shaft sleeve main structure is provided with evenly distributed accommodating cavities. The accommodating cavities are machined to form inner grooves with a semicircular cross-section. The spacing is 0.1 mm and the semicircular diameter is 1.5 mm. The total volume of the accommodating cavities accounts for 30% of the total volume of the shaft sleeve main structure.
[0054] The self-lubricating material used in Example 1 is a uniform mixture of Ti3AlC2 powder and Cu powder, wherein the mass ratio of Ti3AlC2 powder to Cu powder is 40:60, the particle sizes of Ti3AlC2 powder and Cu powder are 5um and 10um respectively, and the purity is both above 99.9%.
[0055] The self-lubricating material is filled into the accommodating cavity of the main structure of the sleeve, which specifically includes the following steps: at room temperature, a mold with an inner diameter of 20.3 mm and a height of 10 mm is selected, the mold includes upper and lower punches and an outer mold, the lower punch is placed in the outer mold, and the mixed powder of the self-lubricating material is filled in, the main structure of the sleeve is placed in the mold, and then the mixed powder of the self-lubricating material is filled in, and then the upper punch is placed in the mold, followed by cold pressing pre-pressing, the strength of the cold pressing is 100 MPa, and the filling amount of the self-lubricating material is 30% of the total volume of the main structure of the sleeve.
[0056] S2. Sintering: Place the pre-pressed mold into a spark plasma sintering furnace for sintering at a temperature of 950°C. Keep the furnace in a vacuum at a degree of 10 -3 Pa, the holding time is 10min, the sintering pressure is 50MPa, and after the holding time, the composite sleeve is cooled to room temperature and taken out to obtain the composite sleeve. Figure 2 As shown, after demoulding, it is measured that the density of the sintered nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve is greater than 99%.
[0057] The microstructure of the composite sleeve prepared in Example 1 was characterized by scanning electron microscopy (SEM). The microstructure of the nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve prepared in Example 1 is as follows: Figure 3 As shown, from Figure 3It can be seen that the area marked as 3 is a Ni-based high-temperature alloy, the area marked as 2 is a transition layer, and the area marked as 1 is a MAX-based self-lubricating material. The average thickness of the transition layer is 10μm. The measured phase structure of the transition layer includes Cu / Ni phase and Ni / Ni3Al phase. The main structure of the Ni-based high-temperature alloy sleeve and the MAX-based self-lubricating structure are tightly combined without gaps. The hardness corresponding to points 1, 2, and 3 in the figure is measured by nanoindentation and is 7.6GPa, 7.3GPa, and 5.7GPa respectively.
[0058] The radial crushing strength of the composite sleeve prepared in Example 1 was tested by a pressure testing machine. The crushing strengths of the nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve of Example 1 at room temperature and at 800°C were measured to be 1050 MPa and 630 MPa, respectively, indicating that the nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve prepared in Example 1 has excellent room temperature and high temperature mechanical properties.
[0059] The friction coefficient of the nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve prepared in Example 1 was tested using an American Brooke friction tester at room temperature and 800°C in air. The friction pair was a high-temperature alloy friction pair, a high-temperature alloy GH4169 ball was used, the friction load was 10N, and the test surface was the inner surface of the composite sleeve. The friction coefficient curve is shown in FIG. Figure 4 The average friction coefficient of the composite sleeve prepared in Example 1 at room temperature was 0.390, and the wear rate was 8.03×10 -5 mm 3 / (N·m); the average friction coefficient at high temperature of 800℃ is 0.185, and the wear rate is 6.56×10 -6 mm 3 / (N·m). The experimental results show that the nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve prepared in Example 1 has excellent self-lubricating properties during the friction process from room temperature to 800°C.
[0060] Example 2
[0061] The difference between Example 2 and Example 1 is that in step S1, the outer diameter of the main structure of the high-temperature alloy sleeve is 30 mm, the inner diameter is 23 mm, and the height is 3 mm. The inner ring of the sleeve body is provided with uniformly distributed accommodating cavities, and the accommodating cavities are semicircular inner grooves with a spacing of 0.1 mm and a semicircular diameter of 2 mm. The total volume of the accommodating cavities accounts for 30% of the total volume of the main structure of the sleeve. The inner diameter of the mold used is 30.3 mm, and the remaining preparation steps are the same as those of Example 1. A nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve is prepared, and the density of the sintered nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve is measured to be above 99%.
[0062] The microstructure of the nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve prepared in Example 2 was characterized by the same test method as in Example 1. It was measured that the nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve prepared in Example 2 included a Ni-based high-temperature alloy, a transition layer and a MAX-based self-lubricating material, the average thickness of the transition layer was 10 μm, and the composition of the transition layer included a Cu / Ni phase and a Ni / Ni3Al phase, and the main structure of the Ni-based high-temperature alloy sleeve and the MAX-based self-lubricating structure were tightly combined without gaps.
[0063] The crushing strength of the nickel-based high-temperature alloy / Ti3AlC2+Cu composite shaft sleeve prepared in Example 2 was tested by the same method as in Example 1, and the crushing strength of the composite shaft sleeve of Example 2 at room temperature and at 800°C was measured to be 1211 MPa and 864 MPa, respectively. It can be seen that the nickel-based high-temperature alloy / Ti3AlC2+Cu composite shaft sleeve prepared in Example 2 has excellent mechanical properties at room temperature and high temperature, and is significantly better than that of Example 1. It is speculated that the reason why the crushing strength of Example 2 is improved compared with that of Example 1 is caused by the improved strength of the main structure of the high-temperature alloy shaft sleeve.
[0064] The friction coefficient of the nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve prepared in Example 2 was tested in the same manner as in Example 1 at room temperature, 600°C and 800°C in air. The friction coefficient curves are shown in FIG. Figure 5 The average friction coefficient of the nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve prepared in Example 2 was measured to be 0.396 at room temperature, and the wear rate was 9.20×10 -5 mm 3 / (N·m); the average friction coefficient at 600℃ is 0.303, and the wear rate is 5.19×10 -5 mm 3 / (N·m); the average friction coefficient at 800℃ is 0.291, and the wear rate is 5.69×10 -6 mm 3 The experimental results show that the nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve of Example 2 has excellent room temperature and high temperature self-lubricating properties, and has no significant change compared with the self-lubricating properties of Example 1.
[0065] Example 3
[0066] The difference between Example 3 and Example 2 is that the sintering temperature in step S2 of Example 3 is 1000°C, and the remaining preparation steps are the same as those of Example 2, to prepare a nickel-based high-temperature alloy / Ti3AlC2+Cu composite shaft sleeve. The density of the sintered nickel-based high-temperature alloy / Ti3AlC2+Cu composite shaft sleeve is measured to be above 99%.
[0067] The microstructure of the nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve prepared in Test Example 3 is as follows: Figure 6 As shown, the nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve prepared in Example 3 includes a Ni-based high-temperature alloy, a transition layer and metal Cu, and a layered structure Ti3AlC2 dispersed in the metal Cu. The average thickness of the transition layer is 15 μm, and the composition of the transition layer includes Cu / Ni phase and Ni / Ni3Al phase. The main structure of the Ni-based high-temperature alloy sleeve and the MAX-based self-lubricating structure are tightly combined without gaps.
[0068] The crushing strength of the composite sleeve of Example 3 was tested by the same method as Example 2, and the crushing strength of the composite sleeve of Example 3 at room temperature and 800°C was measured to be 1179 MPa and 659 MPa, respectively. It can be seen that the composite sleeve prepared in Example 3 has good mechanical properties at room temperature and high temperature, but the mechanical properties are significantly reduced compared with Example 2. It is speculated that the reason for the decrease in strength is that the volume fraction of the γ' phase of the nickel-based high-temperature alloy is reduced under high-temperature sintering.
[0069] The friction performance of the composite sleeve of Example 3 was tested in the same manner as in Example 2. The average friction coefficient of the composite sleeve prepared in Example 3 was 0.48 at room temperature, and the wear rate was 1.2×10 -4 mm 3 / (N·m); the average friction coefficient at high temperature of 800℃ is 0.28, and the wear rate is 8*10 -6 mm 3 / (N·m). The experimental results show that the composite sleeve prepared in Example 3 has good self-lubricating properties at room temperature and high temperature, but the self-lubricating properties are significantly reduced compared with those in Example 2. It is speculated that the main reason is that the reaction between Ti3AlC2 and nickel-based high-temperature alloy increases at high temperature, the width of the generated transition layer increases, resulting in the formation of more hard Ni3Al, which reduces the room temperature lubrication performance.
[0070] Example 4
[0071] The difference between Example 4 and Example 2 is that the total volume of the accommodating cavity in Example 4 accounts for 35% of the total volume of the main structure of the sleeve, the filling amount of the self-lubricating material is 35% of the total volume of the main structure of the sleeve, and the remaining preparation steps are the same as Example 2 to prepare a nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve.
[0072] The microstructure of the nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve prepared in Example 4 was tested and characterized by the same method as in Example 2. It was measured that the nickel-based high-temperature alloy / Ti3AlC2+Cu composite sleeve prepared in Example 4 includes a Ni-based high-temperature alloy, a transition layer and metal Cu, and a layered structure Ti3AlC2 dispersed in the metal Cu, the average thickness of the transition layer is 15 μm, and the composition of the transition layer includes Cu / Ni phase and Ni / Ni3Al phase. The main structure of the Ni-based high-temperature alloy sleeve and the MAX-based self-lubricating structure are tightly combined without gaps.
[0073] The same method as in Example 2 was used to test the crushing strength of the composite sleeve of Example 4, and the crushing strength was significantly lower than that of Example 2. The same method as in Example 4 was used to test the lubrication performance of Example 4, and the self-lubricating performance of Example 4 was significantly lower than that of Example 2. It is speculated that the main reason is that the increase in the filling amount of the self-lubricating material leads to a decrease in the mechanical properties, and the average width of the transition layer increases, resulting in the formation of more hard Ni3Al, which reduces the self-lubricating performance.
[0074] Example 5
[0075] The difference between Example 5 and Example 2 is that in step S1 of Example 5, the sleeve is manufactured by additive manufacturing using Incol738 high-temperature alloy powder to obtain a porous or honeycomb structure matrix skeleton, the skeleton is characterized by evenly distributed round holes and honeycomb grooves in the inner ring. The high-temperature alloy sleeve body is placed in a cemented carbide mold at room temperature, filled with copper and Ti3AlC2 phase metal ceramic mixed powder, and then placed in a spark plasma sintering furnace for sintering at a sintering temperature of 900°C. The furnace body is kept in vacuum and cooled to room temperature with the furnace to prepare a composite sleeve.
[0076] Through the above preparation process, the embodiments of the present invention can obtain a high-temperature alloy-based high-temperature solid lubricating composite sleeve that is dense, has good mechanical properties, is resistant to high temperatures, and has good self-lubricating effect, especially embodiments 1 and 2 have better self-lubricating performance.
[0077] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A MAX phase ceramic-metal-high temperature alloy based self-lubricating composite sleeve, characterized in that: The composite sleeve comprises a sleeve main structure and a self-lubricating structure, wherein the sleeve main structure is a circular ring structure, a receiving cavity to be filled is arranged on the friction surface of the sleeve main structure, and the self-lubricating material is filled and compounded in the receiving cavity on the friction surface of the sleeve main structure to form a self-lubricating structure; wherein the sleeve main structure is made of a high-temperature alloy material, and the high-temperature alloy material comprises at least one of a Ni-based, Co-based, Fe-based, Ti-based, Mo-based, Nb-based or intermetallic compound-based high-temperature alloy; the self-lubricating material comprises a MAX phase metal ceramic component and a metal component; the molecular formula of the MAX phase metal ceramic component is M n+1 AX n , n=1, 2 or 3, M includes at least one of Ti, V, Cr, Zr, Nb, Mo, Hf, Sc or Ta, A includes at least one of Al, Si, P, S, Ga, Ge, As, Cd, In, Sn, Tl or Pb, X is C and / or N; the metal component includes at least one of metal Cu, Ag, Pb, Ti, Al or V; the preparation method of the composite sleeve comprises the following steps: S1. providing a sleeve main structure and a self-lubricating material, the sleeve main structure is a circular ring structure, the friction of the sleeve main structure A receiving cavity to be filled is arranged on the friction surface, and the total volume of the receiving cavity accounts for 20-50% of the total volume of the main structure of the sleeve, and the mixed powder of the self-lubricating material is pre-pressed and filled in the receiving cavity; S2. Sintering molding, sintering the pre-pressed main structure of the sleeve and the mixed powder of the self-lubricating material, and the main structure of the sleeve and the self-lubricating material are metallurgically reacted to form the composite sleeve, and the self-lubricating material is compounded in the receiving cavity on the friction surface of the main structure of the sleeve to form a self-lubricating structure, and the sintering pressure is 40-80MPa.
2. The MAX phase ceramic-metal-high temperature alloy based self-lubricating composite sleeve according to claim 1, characterized in that: The accommodating cavity includes at least one of holes, grooves or interpenetrating network pore structures arranged on the friction surface of the sleeve main structure, and the total volume of the accommodating cavity accounts for 25-40% of the total volume of the sleeve main structure.
3. The MAX phase ceramic-metal-high temperature alloy based self-lubricating composite sleeve according to claim 1, characterized in that: The mass ratio of the MAX phase metal ceramic component to the metal component is 0.5:99.5~99.5:0.
5.
4. The MAX phase ceramic-metal-high temperature alloy based self-lubricating composite sleeve according to any one of claims 1 to 3, characterized in that: The high temperature alloy material includes a Ni-based high temperature alloy.
5. The MAX phase ceramic-metal-high temperature alloy based self-lubricating composite sleeve according to any one of claims 1 to 3, characterized in that: The MAX phase metal ceramic component includes Ti3AlC2 and / or doped (Ti,M')3AlC2, wherein M' includes at least one of Cr, V, Zr or Nb; the metal component includes Cu and / or Cu-M" alloy, wherein M" includes at least one of Ni, Sn, Cr, Nb, Ag, Pb, Ti or Al.
6. The MAX phase ceramic-metal-high temperature alloy based self-lubricating composite sleeve according to claim 5, characterized in that: A transition layer is formed between the shaft sleeve main body structure and the self-lubricating structure, and the average thickness of the transition layer is 3-30 μm.
Citation Information
Patent Citations
Ni-base alloy / ceramic composite material and preparing method thereof
CN105648276A
Metal-based self-lubricating composite material as well as preparation method and application thereof
CN118374712A
Cited By
Method for improving sintering speed and uniformity of composite shaft sleeve copper powder
CN121315283A